Peran Guru Akidah Akhlak dalam Upaya Meningkatkan Akhlakul Karimah Siswa MIN 1 Dairi - Muhammad Sanif (Journal on Education, 2024)
This research aims to identify the morals of students at MIN 1 Dairi and the role of morals teachers in improving the morals of students at MIN 1 Dairi. The research approach chosen is a qualitative method. Using data collection instruments consisting of direct observation, interviews and documentation. The subjects or informants in the research consisted of students at MIN 1 Dairi and Aqidah Akhlak teachers. This research was carried out using a descriptive-qualitative data analysis approach and to ensure the validity of the data, researchers used triangulation techniques. There are two research findings, namely: first, the morals of students at MIN 1 Dairi, where after the learning process, morals while at school is behavior that is continuously monitored by teachers and other school staff. Second, the role of teachers in improving the morals of students at MIN 1 Dairi must be increased in order to achieve better morals and there will be policies taken by the school to improve the morals of these students.